1978
DOI: 10.1161/01.res.43.4.601
|View full text |Cite
|
Sign up to set email alerts
|

Influence of glucose, insulin, and potassium on vulnerability to ventricular fibrillation in the canine heart.

Abstract: SUMMARY We studied the influence of glucose (G), insulin (I) and potassium (K + ) on vulnerability to ventricular fibrillation (VF) of the nonischemic canine myocardium. Vulnerability was assessed by determining VF and repetitive extrasystole (RE) thresholds with a single stimulus applied to the right ventricular endocardium during the vulnerable period. Electrical testing of the heart was performed before and after 1 and 2 hours of infusing G (10 mg/kg per min) and I (0.025 U/kg per min) with and without K + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…211 However, the management of hypokalemia in the setting of cardiotoxicity, specifically torsades de pointes, is largely based on historical case reports that report slow infusion of potassium over hours. 212 The effect of bolus administration of potassium for cardiac arrest suspected to be secondary to hypokalemia is unknown and ill advised (Class III, LOE C).…”
Section: Acls Modifications In Management Of Severe Cardiotoxicity Dumentioning
confidence: 99%
“…211 However, the management of hypokalemia in the setting of cardiotoxicity, specifically torsades de pointes, is largely based on historical case reports that report slow infusion of potassium over hours. 212 The effect of bolus administration of potassium for cardiac arrest suspected to be secondary to hypokalemia is unknown and ill advised (Class III, LOE C).…”
Section: Acls Modifications In Management Of Severe Cardiotoxicity Dumentioning
confidence: 99%
“…In a diabetic rat model, (52), an increased availability of glucose to the cell may have contributed to the raised vulnerability threshold (53) after epinephrine in the conditioned state.…”
Section: Discussionmentioning
confidence: 99%
“…734 Several clinical studies report an association between hypokalemia and the development of VF (LOE 5), 724,[735][736][737] and an animal study reported that hypokalemia lowers the VF threshold (LOE 5). 738 In an animal model of cardiac arrest, it was reported that hyperkalemic animals had a higher rate of survival (LOE 5). 739 …”
Section: Consensus On Sciencementioning
confidence: 99%